2018
DOI: 10.12691/jfnr-6-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity and Quality of Meals: The Saudi School Meal and Home Meal Study SSMHMS – A Cross Sectional Study

Abstract: Epidemiological studies have shown a strong association between childhood obesity and quality of food consumed in schools and at home as well. The objectives of this study are to assess quality of school meals and home meals of children between the age 3 to 5 years old, and their obesity level. A cross sectional study conducted on one hundred and thirty children (3-6 years of age; 73 boys and 57 girls) of a private preschool in Jeddah city .Firstly we assessed children weights using anthropometric measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…14 Dietary habits established in early childhood significantly influence inclination towards junk food in the future, which lead to overweight or obesity, diabetes, and allergies. 15 This study followed the previous work conducted by Dr Eid and colleagues, 3 which assessed one of the main risk factors for obesity; meal quality. However, this study focuses on eating habits and lifestyles, which are regarded as major risk factors and include nutrition awareness, 16 physical activity, 17 consumption of sugary drinks and sweets 18 and low consumption of fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…14 Dietary habits established in early childhood significantly influence inclination towards junk food in the future, which lead to overweight or obesity, diabetes, and allergies. 15 This study followed the previous work conducted by Dr Eid and colleagues, 3 which assessed one of the main risk factors for obesity; meal quality. However, this study focuses on eating habits and lifestyles, which are regarded as major risk factors and include nutrition awareness, 16 physical activity, 17 consumption of sugary drinks and sweets 18 and low consumption of fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…In the recently conducted Saudi School Meal and Home Meal Study (SSMHMS), a meal analysis showed that school meals contain a high amount of carbohydrates, which is also associated with high levels of obesity and overweight children. 3 In addition, other studies have observed that sugar-sweetened carbonated drinks are significantly associated with BMI scores and obesity levels. 25 This is due to the high energy intake and availability, which has critical impact on causing obesity, which is accompanied by low activity levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations